Coronary artery bypass grafting in a patient with hypopituitarism: Report of a case [Hi̇popi̇tui̇tari̇zm'li̇ bi̇r olguda koroner arter baypas cerrahi̇si̇: Vaka sunumu] - (:unkn) unknown (My University, 2009)
Presence of hypopituitarism in patients undergoing coronary artery bypass grafting increases the risks related to both anesthesia and surgery. Perioperative replacement of adrenocortical and thyroid hormones in appropriate amounts plays a vital role in the management of such patients. In this paper successful coronary artery bypass grafting in a patient with hypopituitarism is presented and the perioperative management strategy in these patients is discussed.
Keywords: Adrenocortical hormone; Coronary artery bypass grafting; Hypopituitarism; Thyroid hormones